PENERAPANKONSEP TAYSÎRDALAM SISTEM EKONOMI ISLAM - Andi Iswandi (AHKAM : Jurnal Ilmu Syariah, 2014)
Application of Taysîrin The Islamic Economic System. Studies about the taysîrconcept are still minimal but taysîrhas a significant function in addressing issues of Islamic law, particularly in the field of mu’âmalah. In the field of mu’âmalah, the taysîrconcept is not only needed, moreover it is a ‘cure’ in necessity to heal the morbidity of heretical behaviour in business and economics. Taysîrhas also become the answer for groups of people who are contradictory when addressing the Shari’a law. Taysîrdoes not provide answers and support groups who are rigid against Shari’a law (al-mutasyaddid) and also does not provide answers and support groups who undermine the law (al-mutasâhil).DOI: 10.15408/ajis.v14i2.1283